2017
DOI: 10.1007/s00238-017-1308-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the foreign body response to common surgical biomaterials in a murine model

Abstract: Background Implanted biomaterials are subject to a significant reaction from the host, known as the foreign body response (FBR). We quantified the FBR to five materials following subcutaneous implantation in mice. Materials and methods Polyvinyl alcohol (PVA) and silicone sheets are considered highly biocompatible biomaterials and were cut into 8mm-diameter disks. Expanded PTFE (ePTFE)and polypropylene are also widely used biocompatible biomaterials and were cut into 2cm-long cylinders. Cotton was selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 26 publications
2
48
0
1
Order By: Relevance
“…Mast cells are thought to be attracted by foreign body reactions and may attract macrophages through degranulation, maintaining and priming the inflammatory response in previous animal models. 16 Further studies are needed to investigate these mechanisms in patients with face mask-related IR.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are thought to be attracted by foreign body reactions and may attract macrophages through degranulation, maintaining and priming the inflammatory response in previous animal models. 16 Further studies are needed to investigate these mechanisms in patients with face mask-related IR.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton on the other hand, has been shown to induce intense FBRs and also produced the most vertical MBL in the present review. Even though cotton is generally avoided in vivo, it has sometimes been used as a negative control in studies that compared the FBR to different biomaterials [32]. From reports on iatrogenic injuries following surgery, it is known that retained sterile cotton sponges can cause large lesions of foreign body type in both hard and soft tissues, sometimes referred to as “cottonballomas”.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro culture of human mast cell lines has demonstrated that interaction in the decellularized extracellular matrix (ECM) microenvironment promotes mast cell differentiation, maturation, and viability compared to collagen controls ( 9 ). However, in vivo studies have mainly just evaluated shifts in mast cell numbers associated with biomaterial deployment, though their general low numbers in tissue make it difficult to determine conclusive results from this approach ( 10, 11 ). Early studies with synthetic materials have focused on their functional role and mainly produced results characteristic of a classical mast cell phenotype highlighting contributions to early acute inflammatory cell infiltration ( 2 ), and fibrous capsule formation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this immunomodulatory influence associated with improved tissue outcomes has been rigorously evaluated with macrophage 5,6 and T cell populations 7,8 , potential contribution of mast cells to the immunomodulatory effect of naturally derived biomaterials has been largely ignored. Studies have mainly just evaluated shifts in mast cell numbers associated with biomaterial deployment, though their general low numbers in tissue make it difficult to determine conclusive results from this approach 9,10 . Early studies with synthetic materials have focused on their functional role and mainly produced results characteristic of a classical mast cell phenotype highlighting contributions to early acute inflammatory cell infiltration 2 , and fibrous capsule formation 11 .…”
mentioning
confidence: 99%